Visualidades do espaço escolar: uma interlocução com a cultura visual - Mendonça, Maria Goreti Cortes (2011)
The present paper discusses about an experience on education in the teaching of visual arts accomplished at school with a group of five students in the first grade of high school in Marco Polo School in Santa Maria/RS. This study utilizes the language of graffiti for questioning the visual features of school environment. Teacher and students interact in an educational process grounded on the scope of visual culture. The education of the visual culture by presenting a multidisciplinary character makes possible interrelationships of spaces and convergence as a field of knowledge, permeated by visual. The research was supported in Research Based in the Arts (IBA) or Arts Based Research (ABR), which is a type of qualitative research approach and it is not focused on the researcher or the researched object, but as a researcher, developer, reader can write and build that together. The most important authors participating in this theoretical construct are: HERNANDEZ (2000, 2007, 2008), Martins (2004, 2007) and MIRZOEFF (2003) regarding the field of visual culture; Lazzarini (2007) and Silva (2005) with reference to graphite, and Costa (2009), SILVA (2000, 2000a) and Pereira (2010), concerning the space to the school. These influences are brought by the survey are still settling into other possibilities. Among the results, it can be highlighted the new learning as a collective group that covered the meetings with new textures with different views, trying to rephrase things and try other ones, mainly to build a space for dialogue to discuss art.